Pembelajaran Berbasis Audio Visual pada Materi Teks Biografi di Kelas X SMA - Khadijah, Khadijah; Safina, Nila; Rita, Rita (Medan Resource Center, 2023)
This study aimed to develop and assess the validity and feasibility of audio-visual-based learning media for Listening Biography Texts in Class X SMA/MA during the Covid-19 period. The development process followed the model proposed by Stephen M. Alessi and Trollip, encompassing planning, design, and development stages. The results revealed that the audio-visual-based learning materials obtained high feasibility ratings from material experts (82%